'El Mediterráneo europeo': Una imagen de marca común frente a los países lejanos para los destinos tradicionalmente turísticos de la Unión Europea - Mercedes Jiménez García (Colegio de Economistas de A Coru\~na, 2008)
– Today tourism is one of the economic fields with a bigger contribution to the GDP in some countries. Lately these countries have witnessed how this industry became key to their economy. France, Spain Italy and Greece too, the so-called 'Mediterranean Arch' stand out within the framework of the European Union. However, due to the dynamic character of this sector and in order to maintain its power of attraction, the implementation of constant strategies of improvement and renewal is required, in order to face an increasingly stronger competition. For this reason, we are using a Branding strategy applied to the most remote areas of these tourist destinations under a common Mediterranean tag.
Keywords: 330; Turismo; Mediterráneo; marca; branding; Unión Europea; UE; encuestación